Effect of selective pre-oxidation on the growth and corrosion resistance of hot-dip zinc coating of nodular cast iron. (1st July 2021) - Wu, Hui; Peng, Haoping; Liu, Ya; Tu, Hao; Wang, Jianhua; Su, Xuping
Highlights: Selective pre-oxidation of nodular cast iron can be realized by controlling the equilibrium oxygen partial pressure. Si element on the surface of nodular cast iron is transformed into SiO2 by selective pre-oxidation. The reduction of silicon content on the surface of nodular cast iron can improve the corrosion resistance of the coating. Abstract: When pre-oxidation is carried out at 800 °C and 1 atm, only ordinary oxidation occurs on the surface of nodular cast iron, and the main pre-oxidation product is Fe2 O3 . The oxidation of nodular cast iron following pre-oxidation at 800 °C and low oxygen pressure is selective and the main pre-oxidation product is SiO2 . After the selective pre-oxidation treatment, the corrosion current density of the ζ layer of nodular cast iron is significantly reduced, and its impedance response is significantly increased.